2020
DOI: 10.1128/iai.00323-20
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2-Tpl2-Dependent ERK Signaling Drives Inverse Interleukin 12 Regulation in Dendritic Cells and Macrophages

Abstract: This study investigated responses to Toll-like receptor 2 (TLR2)-driven extracellular signal-related kinase (ERK) signaling in dendritic cells (DCs) versus macrophages. TLR2 signaling was induced with Pam3Cys-Ser-Lys4, and the role of ERK signaling was interrogated pharmacologically with MEK1/2 inhibitor U0126 or genetically with bone-marrow-derived macrophages or DCs from Tpl2-/- mice. We assessed cytokine production via ELISA or V-PLEX, and mRNA levels were assessed via qRT-PCR. In macrophages, blockade of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“… 25 ERK signaling is also involved in the production of tumor necrosis factor α and interleukin-10 in myeloid dendritic cells. 18 In addition, Groft and co-workers 26 reported that the toll-like receptor 2 transduces ERK signaling and mediates the induction of interleukin-12, which may promote the priming of Th1 responses in dendritic cells. Knowledge of DC-SIGN-mediated ERK signaling is currently accumulating, 27 although these reports suggest that ERK signaling has an essential role in the immune responses of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“… 25 ERK signaling is also involved in the production of tumor necrosis factor α and interleukin-10 in myeloid dendritic cells. 18 In addition, Groft and co-workers 26 reported that the toll-like receptor 2 transduces ERK signaling and mediates the induction of interleukin-12, which may promote the priming of Th1 responses in dendritic cells. Knowledge of DC-SIGN-mediated ERK signaling is currently accumulating, 27 although these reports suggest that ERK signaling has an essential role in the immune responses of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…While reduction of pro-inflammatory mediators may limit inflammation associated tissue damage, there was also a moderate reduction in IL-10, which has anti-inflammatory effects. It was previously demonstrated that murine macrophages treated with the MEK1/2 inhibitor U0126 resulted in a decrease in Il10 expression following Pam3CSK4 stimulation with a corresponding increase in Il12p40 (Il12b) expression ( Groft et al., 2020 ). We did not observe significant reduction of Il12a or Il12b expression in macrophages treated with MEK1/2 inhibitors following either LPS, Pam3CSK4, or FSL1 stimuli, with modest trends towards increased expression.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may reflect the different cell types studies. Indeed, signalling pathways downstream of TLR2 have previously been observed to be divergent in DCs in macrophages (Groft et al, 2020), implying differential regulation of TLR-induced cytokine responses in different myeloid cells. In support of this hypothesis, Ifitm3 has no impact on MCMV-induced cytokine responses by murine macrophages (Stacey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%